Extremely rapid and simple healing of a transparent conductor based on Ag nanowires and polyurethane with a Diels–Alder network. Issue 5 (8th January 2016) - Pyo, Kyoung-hee; Lee, Da Hee; Kim, Youngmin; Kim, Jong-Woong
Abstract : A transparent electrode comprising Ag nanowires and a polyurethane equipped with Diels–Alder adducts as crosslinkers was successfully fabricated to realize a rapidly amendable electrode. Abstract : A transparent electrode comprising Ag nanowires (AgNWs) and a polyurethane equipped with Diels–Alder adducts as crosslinkers was successfully fabricated to realize a thermally amendable electrode. To bury the AgNWs at the surface of the polymer, we designed an effective transfer method using a Kapton film as a preliminary supporter and employing a roller-based laminator equipped with a heater. Intense pulsed light (IPL) was employed to provide localized heat to the AgNW–polymer composite layer. By virtue of the efficient heating mechanism, a composite electrode that was separated by a knife could be healed and its conductivity recovered in a very short period of less than 1 ms. Only one or two 500 μs pulses of IPL were enough to effectively repair the damaged electrodes. Owing to the reversible Diels–Alder reaction, reproducible healing was also observed.